Modal salient belief and social cognitive variables of anti-doping behaviors in sport: Examining an extended model of the theory of planned behavior - Chan, Derwin; Hardcastle, Sarah; Dimmock, J.; Lentillon-Kaestner, V.; Donovan, Robert; Burgin, M.; Hagger, Martin (Elsevier BV, 2015)
Objectives: This study examined the modal salient behavioral, normative, and control beliefs within the theory of planned behavior (TPB) in the context of anti-doping in sport. We tested the efficacy of four hypothesized expectancy-value models as predictors of the directly-measured social-cognitive components of the TPB toward doping avoidance: attitude, subjective norm, perceived behavioral control (PBC), and intention.Methods: After developing the belief-expectancy and belief-value of modal salient beliefs items based on a pilot belief-elicitation study of young elite athletes (N ¼ 57, mean age ¼ 18.02), 410 young athletes (mean age ¼ 17.70) completed questionnaire items of the modal salient beliefs and direct measures of the social-cognitive components of doping avoidance. Variance-based structural equation modeling was used to examine the four proposed expectancy-value models.Results: Belief-expectancies, belief-values, and the expectancy-belief multiplicative composites formed positive associations with their corresponding social cognitive variables. The model in which belief expectancies were the sole predictors of the social cognitive provided the most parsimonious and reliable model to explain the relationship between modal salient beliefs and directly-measured social cognitive variables for doping avoidance in sport.Conclusion: Belief-expectancies including behavioral belief strength (e.g., “doping avoidance is likely to ease the worry of being caught doping”), normative belief strength (“my coach thinks that I should avoid doping”) and control belief strength (“I expect I have power to ‘say no’ to doping”) are the belief-based components that underpin direct measures of the social-cognitive variables from the TPB with respect to doping avoidance.